Determinants of left ventricular untwisting behaviour in patients with dilated cardiomyopathy: analysis by two-dimensional speckle tracking. Issue 4 (18th September 2008) - Saito, M; Okayama, H; Nishimura, K; Ogimoto, A; Ohtsuka, T; Inoue, K; Hiasa, G; Sumimoto, T; Funada, J; Shigematsu, Y; Higaki, J
Abstract : Background/objective: Left ventricular (LV) untwisting velocity has emerged as a novel index of LV diastolic function since it is thought to be related to LV diastolic suction. However, the pathophysiology of LV untwisting behavior has not been fully investigated. The aim of this study was to investigate the determinants of LV peak untwisting velocity in patients with dilated cardiomyopathy (DCM). Methods: 101 patients with DCM (mean age 60 (SD 13) years) and 50 control subjects were evaluated. After a standard echocardiographic examination, peak torsion and peak untwisting velocity were measured using two-dimensional speckle-tracking imaging. Radial dyssynchrony was assessed by speckle-tracking radial strain analysis. Tissue Doppler derived systolic (Ts-SD) and diastolic (Te-SD) dyssynchrony indices were also assessed. Results: The patients with DCM had significantly smaller peak torsion (p<0.001) and peak untwisting velocity (p<0.001) and greater radial dyssynchrony (p<0.001) and Ts-SD (p<0.001) and Te-SD (p = 0.001) compared with the control subjects. The peak untwisting velocity was correlated with end-systolic volume index (r = 0.524, p<0.001), E/e′ (r = 0.365, p<0.001), radial dyssynchrony (r = 0.578, p<0.001), Ts-SD (p<0.001), Te-SD (p<0.001) and peak torsion (r = −0.635, p<0.001) in patients with DCM . Multivariate analysis revealed that peak torsion, radial dyssynchrony and E/e′ were independent predictors of peak untwisting velocity in patients with DCM (standard coefficient −0.483, p<0.001, 0.330, p<0.001 and 0.241, p = 0.001, respectively). Conclusion: These results suggest that strain-based LV radial dyssynchrony and E/e′ as well as LV torsion are related to diastolic untwisting behaviour in patients with DCM.